Posisi Tawar Perempuan Dalam Rumah Tangga: Studi Kasus Buruh Pabrik di PT. Kayu Lima Sejahtera - Sari, Norma; Damaiyanti, Varinia Pura; Hakim, Arif Rahman (Prodi Sosiologi FISIP ULM, 2024)
Women today must carry out their duties as housewives and must also work to help the family economy. This study aims to analyze the causes of the dual role of women in Anjir Serapat Village, and to determine the position of women who work in their families. This research uses a qualitative approach with the type of field research. The research was conducted on female laborers at PT Kayu Lima Sejahtera in Anjir Serapat Tengah Village, East Kapuas District, Kapuas Regency, Central Kalimantan. Data collection techniques using observation, interviews and documentation. Data analysis techniques through the stages of data reduction, data presentation and conclusion drawing. The results show that women work as laborers to help meet household needs, which has an impact on financial sufficiency and helps create household harmony. However, this does not always have a positive impact, but also has a negative impact on women because they have to feel exhausted due to having to do household chores. Family time is also reduced, which makes their children more independent and able to understand their parents' work, regardless of their young age. This research shows that the existing social construction in society about the role of a good wife only around the domestic can be broken. In the Anjir Serapat Village community, it is women who hold a more dominant public role.